PENGARUH MOTIVASI INTRINSIK, KOMPETENSI AUDITOR DAN KEPUASAN KERJA TERHADAP KINERJA AUDITOR EKSTERNAL (SURVEI PADA AUDITOR BPK-RI PERWAKILAN PROVINSI SULAWESI UTARA) - Neghe, Iriany; Sondakh, Jullie; Kalalo, Meily (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Auditor’s performance is an important thing in order to reflect the quality of work done by auditor in conducting the examination of financial statements objectively. This research is aimed to determine the influence of intrinsic motivation, competence of auditor and job satisfaction on external auditor’s performance. Sample on this research are auditors that work in Indonesia’s Supreme Audit Institution Representative of North Sulawesi Province. The data in this research is primary data that collected by using questionnaires given to auditors. The method of analysis that used to test the hypothesis is multiple regression analysis using SPSS version 23. The result showed that intrinsic motivation has a positive effect on external auditor’s performance, auditor’s competence has a positive effect on external auditor’s performace, job satisfaction has a positive effect on external auditor’s performance. Beside that, intrinsic motivation, auditor’s competence and job satisfaction simultaneously effect the external auditor’s performance.  Keywords: Intrinsic Motivation, Auditor’s competence, Job Satisfaction, External Auditor Performance.